2006
DOI: 10.1097/01.sla.0000246834.07130.5d
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective, Randomized, Controlled Trial Comparing Intermittent Portal Triad Clamping Versus Ischemic Preconditioning With Continuous Clamping for Major Liver Resection

Abstract: Both IP and IC appear to be equally effective in protecting against postoperative liver injury in noncirrhotic patients undergoing major liver resection. However, IP is associated with lower blood loss and shorter transection time. Therefore, both strategies can be recommended for noncirrhotic patients undergoing liver resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
167
2
9

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(187 citation statements)
references
References 36 publications
9
167
2
9
Order By: Relevance
“…[10][11][12][13][14][15] In laboratory animals and humans, IPC of the liver may be induced either by a single short period of ischemia or multiple short cycles of ischemia (or intermittent hilar clamping). 16 In a rat liver transplant model, Yin et al 2 investigated single IPC periods ranging between 5 and 20 minutes and showed that 10 minutes induced the best protection. Although 10 to 15 minutes of RP after the preconditioning ischemia has become a methodological tradition following the initial laboratory work, more recent work by Glanemann et al, 17 in rat liver warm ischemia, showed that 30 to 45 minutes of RP were more effective than 5 to 15 minutes.…”
mentioning
confidence: 99%
“…[10][11][12][13][14][15] In laboratory animals and humans, IPC of the liver may be induced either by a single short period of ischemia or multiple short cycles of ischemia (or intermittent hilar clamping). 16 In a rat liver transplant model, Yin et al 2 investigated single IPC periods ranging between 5 and 20 minutes and showed that 10 minutes induced the best protection. Although 10 to 15 minutes of RP after the preconditioning ischemia has become a methodological tradition following the initial laboratory work, more recent work by Glanemann et al, 17 in rat liver warm ischemia, showed that 30 to 45 minutes of RP were more effective than 5 to 15 minutes.…”
mentioning
confidence: 99%
“…Accordingly, the intermittent clamping of the hepatic pedicle proved to be more effective in attenuating ischemia-reperfusion injury compared to the continuous portal triad clamping 7 . In this context, the interest in hyperbaric oxygen therapy (HBO) has grown due to its role in ischemia and reperfusion injury therefore in the liver transplantation field 9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…There is not a consensus approach of which method is the best for clamping the hepatic pedicle and many authors present different results 4,21,23 . The Cochrane Institute for Systematic Reviews published a paper in 2007 showing the evidence that intermittent clamping is safe but it does not decrease the morbidity of the procedure without any clinical evidence appearing until that date 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Was observed that these animals tolerate ischemia for 60 minutes with low mortality and submitting them to intermittent ischemia produces no mortality 18 . Different models of intermittent ischemia have been described and was chosen one of them in this study, considering that after 10 to 12 minutes of ischemia, three to five minutes of reperfusion are sufficient to restore the intra-hepatic tissue oxygenation 6,23,28 . In this study, the difference between total ischemic time of the ischemia in the continuous and intermittent groups (60 versus 48 minutes) occurred to mimic the real clinical situations experienced during the surgical procedures 4 .…”
Section: Discussionmentioning
confidence: 99%